2020
DOI: 10.1002/etc.4831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non‐native Fish on Lacustrine Food Web Structure and Mercury Biomagnification along a Dissolved Organic Carbon Gradient

Abstract: Although the introduction of non-native fish species has been shown to alter trophic ecology in aquatic ecosystems, there has been limited research on how invasive species alter methylmercury (MeHg) biomagnification in lacustrine food webs. We sampled surface water and biota from 8 lakes in Quebec, Canada, spanning a range of dissolved organic carbon (DOC) concentrations (2.9-8.4 mg/L); 4 lakes were inhabited by native brook trout (Salvelinus fontinalis), and the remaining lakes contained brook trout and a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The long list of studies to date that have examined sh Hg following species invasions and found little to no effect have often invoked the concept of growth altering sh Hg to explain their results (e.g., Johnston et al 2003;Hogan et al 2007; Barst et al 2020), but our study is one of the very few to explicitly evaluate the potential impact of invasive species on sh growth in modulating sh Hg concentrations. While 'growth dilution' is commonly invoked as an explanatory factor in reduced sh Hg in the literature, studies clearly demonstrating evidence for increased conversion e ciency leading to reduced Hg concentrations in sh are infrequent (Trudel and Rasmussen 2006), and actual empirical demonstrations of the process are similarly scarce (see Ward et al 2010 as a rare example).…”
Section: Discussionmentioning
confidence: 99%
“…The long list of studies to date that have examined sh Hg following species invasions and found little to no effect have often invoked the concept of growth altering sh Hg to explain their results (e.g., Johnston et al 2003;Hogan et al 2007; Barst et al 2020), but our study is one of the very few to explicitly evaluate the potential impact of invasive species on sh growth in modulating sh Hg concentrations. While 'growth dilution' is commonly invoked as an explanatory factor in reduced sh Hg in the literature, studies clearly demonstrating evidence for increased conversion e ciency leading to reduced Hg concentrations in sh are infrequent (Trudel and Rasmussen 2006), and actual empirical demonstrations of the process are similarly scarce (see Ward et al 2010 as a rare example).…”
Section: Discussionmentioning
confidence: 99%